Simulation of a biomimetic façade using TRNSYS. (1st March 2018) - Webb, Matthew; Aye, Lu; Green, Ray
Highlights: Biomimicry was employed to improve thermal performance of building facades. Animal fur and blood perfusion were selected as biological models. Fur parameters were optimised to maximise thermal performance. Biomimetic initiatives were integrated in a conventional building facade design. Biomimetic designs could reduce 17% energy consumption to a conventional approach. Abstract: Biomimicry – innovation inspired by nature – is a creative methodology that translates characteristics from the biological world to the domain of human technology. Functional biomimicry offers opportunities to advance the development of flexible building facades. Following biomimetic principles, external fur and bioheat transfer (blood perfusion) and were combined into a mathematical model of a commercial office building façade for a west-facing wall of an office building situated in Melbourne, Australia. TRaNsient SYstem Simulation (TRNSYS) software tool was used to determine temperatures and heat transfer of this biomimetic façade in summer design conditions compared to a reference. The biomimetic façade was simulated to provide cooling of greater than 50 W m −2 and reduced mean surface temperatures in the occupied zone by 2.8 °C, compared with the reference.